Potential of Pandanus Odorifer (Sea Pandan) Fruit as a Supplement to Increasing Chicken Appetite - Hermansyah Amir; Nurhamidah; Sura Menda Ginting; Wike Suviolamei; Yosie Andriani HS (The University of Mataram, 2022)
Pandanus odorifer (sea pandanus) is a plant that is commonly found in Bengkulu coastal areas, and research on this plant has not been done much. The results of previous studies show that sea pandanus with Pandanus tectoricus species contains primary and secondary metabolite compounds, especially in fruit that can be used as antioxidants, anti-bacteria, and others. This study aims to utilize unused P.odorifer fruit as a supplement to increase the appetite for Broiler chicken. Test animals used in the research are 7-day-old Broiler chickens. The P.odorifer samples used as supplements were obtained on the Sungai Suci Bengkulu Tengah Coast. Chickens were given four treatments, P0 control (1mL aquades/day), P1 supplement dose (0.5g/10mL), P2 dosing supplements (1g/10mL), and P3 dose supplement (1.5g/10mL). In general, the study results showed that P.odorifer fruit has the potential to be used as a supplement to increase the appetite of Broiler chicken, with a fat content of 3.92%, carbohydrate of 58.08%, and protein of 2.13%. The study results showed a significant effect of supplementation P.odorifer on Broiler chicken appetite, which was characterized by increasing body weight and eating portions. T-test results of the body weight and portion of the control group and the treatment group, the value of sig (2-tailed) ρ: 0.021 and sig (2-tailed) ρ: 0.016 and with value (α): 0.05, value ρ <α. And based on the results of the Completely Randomized Design analysis, the increase in the effect of P.odorifer supplements on Broiler chicken appetite is maximum at a concentration of 1.5gr/10mL weighing the 20 days of treatment with an F value <0.05.